2006
DOI: 10.1159/000094988
|View full text |Cite
|
Sign up to set email alerts
|

Renal Effects of HMG-CoA Reductase Inhibition in a Rat Model of Chronic Inhibition of Nitric Oxide Synthesis

Abstract: Background/Aims: In addition to their lipid-lowering effects, HMG-CoA reductase inhibitors (statins) induce a variety of pleiotropic actions that have been recently studied in the area of cardiovascular and renal protection. In the present studies we sought to determine whether statins retain beneficial effects in the experimental model of NO deficiency achieved by chronic administration of a pressor dose of L-arginine analogue N-nitro-L-arginine-methyl ester (L-NAME). Methods: To address this issue, blood pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…Recent experimental and clinical studies demonstrated that these effects of statins, called pleiotropic effects, contribute to renal protection [11,25,26,33] . In this study, pitavastatin significantly improved indices of diabetic nephropathy, such as urinary protein excretion, plasma creatinine, and CCr.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experimental and clinical studies demonstrated that these effects of statins, called pleiotropic effects, contribute to renal protection [11,25,26,33] . In this study, pitavastatin significantly improved indices of diabetic nephropathy, such as urinary protein excretion, plasma creatinine, and CCr.…”
Section: Discussionmentioning
confidence: 99%
“…nitric oxide bioavailability, attenuating production of reactive oxygen species, and protecting against complement-mediated injury [31]. In addition, experimental data have shown that statins exert renoprotective effects in a rat model of long-term inhibition of nitric oxide synthesis by amelioration of vascular endothelial growth factor expression and decrease of RhoA activity [32].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that the statin-upregulated nitric oxide system in the kidney, especially in the renal medulla, may contribute to the antihypertensive effect of statins through increased medullary blood flow and inhibited Na reabsorption in the medullary TAL and collecting duct of SHRs. Indeed, several studies reported that statins did not reduce the blood pressure in L-NAME-induced hypertensive rats [40,41] or angiotensin II-treated eNOS knockout mice [42]. Nitric oxide-dependent mechanisms have important roles not only in the antihypertensive effect of statins but also in the renoprotective effect of statins.…”
Section: Discussionmentioning
confidence: 99%
“…rats [40,41] and angiotensin II-treated eNOS knockout mice [42]. Inhibition of Rho/Rho-kinase pathway by statins may contribute not only to the upregulation of eNOS expression and activity but also to benefits in cardiovascular disease [44].…”
Section: Discussionmentioning
confidence: 99%